The gene NCE103 (YNL036w) from Saccharomyces cerevisiae encodes a functional carbonic anhydrase and its transcription is regulated by the concentration of inorganic carbon in the medium - Müller, Dominik; et al. (Molecular Microbiology, 2005)
Carbonic anhydrase (CA) catalyses the rapid interconversion between CO2 and HCO3-. Despite its wide distribution among living organisms, the presence of CA in fungi has been controversially discussed. Using mass spectrometric analysis of O-18 exchange from doubly labelled CO2, we were able to measure CA activity in intact cells of Saccharomyces cerevisiae. Intracellular CA activity was lacking in the Delta nce103 mutant, indicating that NCE103 encodes a functional CA. This was proven by overexpressing and purification of the NCE103 gene product showing a specific activity of around 6900 units per mg protein. Interestingly, the in vivo CA activity was 10-20 times higher in cells grown on low inorganic carbon (Ci; air containing 0.035% CO2) than in high-Ci cells (grown on 5% CO2). The enhanced CA activity of low-Ci cells was inducible after transferring high-Ci cells to air. Northern blot analysis revealed that that expression of NCE103 is transcriptionally regulated by low Ci which was also demonstrated by fusing the NCE103 promoter to beta-galactosidase as a reporter gene. Inactivation of NCE103 results in a high CO2 requiring mutant indicating that a functional CA is an important prerequisite for S. cerevisiae to grow under low-Ci conditions.